Effect of seed treatments and time of inoculation on nodulation and yield of soybeans - Mahmoud, S. A.Z.; Abdel-Nasser, M.; Ali, F. S. (Pesquisa Agropecuaria Brasileira, 2014)
Two field experiments were run using various seed treatments in attempt to obtain successful nodulation and yield of 'Harosoy' soybean (Glycine max (L.) Merrill). Soaking ‘Harosoy' soybean seeds in the inoculum R. japonicum E 45 for three hours or germinating the seeds (by, washing with tap-water for five minutes every one hour and removal of excess water from seed-container) for 3, 6, 12 or 24 hours (12 hrstreatment was the beat) and inoculation with R. japonicum E 45 just before sowing resulted in obtaining successful nodulation and yield: This was indicated by the formation of appreciable high number of nodules on 45, 55, 65, 75 or 85th days after sowing. On harvest, dry weight of the resulting seeds and of whole yield and total-N content of seeds and whole yield as well as dry weight of 100 seeds were substantially higher as compared with control non-inoculated treatments (or even inoculated after 10, 15 or 20 days after sowing).